2009
DOI: 10.3945/ajcn.2009.27981
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetic behavior of the soy isoflavone metabolite S-(-)equol and its diastereoisomer R-(+)equol in healthy adults determined by using stable-isotope-labeled tracers

Abstract: The high bioavailability of both diastereoisomers contrasts with previous findings for the soy isoflavones daidzein and genistein, both of which have relatively poor bioavailability, and suggests that low doses of equol taken twice daily may be sufficient to achieve biological effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 56 publications
6
68
0
1
Order By: Relevance
“…The reservoir forming properties of equol in the epidermis may be due to its lipophilic characteristics where its octanol-water partition coefficient is 3.20, which is higher than other polyphenolic molecules (Rothwell et al, 2005). Additionally, intestinal absorption data support this proposition where equol (either as the R-or S-isomer) has the highest absorption levels (80-85%) compared to other isoflavonoids, such as genistein (at 15-20%) or daidzein (at 30-40%) (Setchell et al, 2009;Setchell & Clerici, 2010). Drug-delivery studies have shown the more stable isomer is R-equol versus S-equol (Alvira et al, 2008) and in vitro culture data suggest that the R-isomer accounts for the chemoprotective effects of equol rather than the S-isomer in breast and prostate cancer cells (Magee et al, 2006).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The reservoir forming properties of equol in the epidermis may be due to its lipophilic characteristics where its octanol-water partition coefficient is 3.20, which is higher than other polyphenolic molecules (Rothwell et al, 2005). Additionally, intestinal absorption data support this proposition where equol (either as the R-or S-isomer) has the highest absorption levels (80-85%) compared to other isoflavonoids, such as genistein (at 15-20%) or daidzein (at 30-40%) (Setchell et al, 2009;Setchell & Clerici, 2010). Drug-delivery studies have shown the more stable isomer is R-equol versus S-equol (Alvira et al, 2008) and in vitro culture data suggest that the R-isomer accounts for the chemoprotective effects of equol rather than the S-isomer in breast and prostate cancer cells (Magee et al, 2006).…”
Section: Discussionsupporting
confidence: 66%
“…Further research has revealed that equol concentrations in low-soy consuming US populations reflect equol intakes from mammalian (cow) milk sources (Frankenfeld, 2011;Hoikkala et al, 2007;Mustonen et al, 2009) that can be as high as 1.5 mg/kg in cow's milk (Höjer et al, 2012). Notably, the metabolism of Rand S-equol in humans appears to be similar (Setchell et al, 2005(Setchell et al, , 2009. Therefore, humans are exposed to this polyphenolic compound from different plant and food sources regardless of age, gender, or geographical location with scientific data to support a consumption/exposure record that appears to be safe (Frankenfeld, 2011;Lephart, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…40,41 Overall, apparent bioavailability of these isoflavones are similar. Nonetheless, the rates of absorption of the isoflavones daidzein and genistein as glycosides are distinctly different from those of daidzein and genistein in their aglycone form and this has recently been suggested to be an important difference that could influence the ultimate efficacy of isoflavones.…”
Section: Bioavailability and Pharmacokineticsmentioning
confidence: 86%
“…Maximum plasma S-equol concentrations occur between 1 and 3 hours after oral administration and it is cleared from plasma with a half-life of 7 to 10 hours. 23,29,32,33 Consequently, over 80% of S-equol is excreted in the urine within 24 hours after administration. 23,32,33 Based on these pharmacokinetics to achieve sustained steady-state serum concentrations, a twice-daily dose, rather than a once-daily dose of S-equol is considered optimal.…”
Section: General Backgroundmentioning
confidence: 99%